Integration of the Power Corridor Concept in the Early-Phase Design of Electric Naval Ships using Mathematical Design Models - Trincas, Giorgio; Braidotti, Luca; Vicenzutti, Andrea; Tavagnutti, Andrea Alessia; Cooke, Chathan M.; Chalfant, Julie; Bucci, Vittorio; Chryssostomidis, Chryssostomos; Sulligoi, Giorgio (International Marine Design Conference, 2024)
The aim of this paper is to illustrate the process of identifying the ‘best compromise’ solution for an all-electric destroyer at the concept design level. The design strategy reflects a paradigm shift from a sequential approach towards a holistic multicriterial approach. The destroyer is required for an extensive range and endurance, fully operable in rough sea states. A mathematical design model (MDM) that includes a set of metamodels, is implemented to evaluate the overall performance of feasible, then non-dominated designs. The power corridor concept is integrated into the MDM to optimize the location and functionality of the individual units of the power train. The fuzzy sets theory is used for normalizing and weighing incommensurable properties of candidate designs, so resolving many of the ill-defined requirements and criteria. The final result of this study is a top-level specification for the destroyer with enhanced performance and reduced power demand.